β-Sitosterol-3-O-β-D-Arbinofuronosyl (1→4)-O-L- Rhamnopyranosyl (1→4)-O-β-D-Glucopyranoside from Roots of Agave americana Linn - Chouhan, R.P.S.; Lal, L.M. (Asian Journal of Chemistry, 2010)
Present communication describes the isolation and identification of a new saponin β-Sitosterol-3-O-β-D-arbniofuranosyl-(1→4)-O-α-L-rhamnopyranosyl (l→4)-O-β-D-glucopyranoside from its root.